2010
DOI: 10.1136/ip.2010.029215.450
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a celebrity death on children's injury-related emergency department visits

Abstract: Background Following a skiing-related head injury death of the actor Natasha Richardson, we noted a marked increase in injury-related visits to the Emergency Department (ED) of the Montreal Children's Hospital (MCH). We assumed these visits were driven by media coverage, which would be greater in Quebec than elsewhere in Canada. Methods Using data from the Canadian Hospitals Injury Reporting and Prevention Program (CHIRPP), we compared visits to the MCH-ED for 10 weeks beginning in March. We also compared visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…During the weeks following the death of actor Natasha Richardson, a 60% increase in emergency room visits at the Montreals Children's Hospital was found in a study by Keays and Pless. 7 These authors concluded that the media coverage of this celebrity death may have generated anxiety among parents, prompting those who might not otherwise have sought medical care to bring their children to the emergency room. 7 The increase in helmet use in people older than 15 years by 12% and by 18% in provinces with and without helmet mandatory, respectively, might partly be due to the fact that parents using ski helmets are role models for their children.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…During the weeks following the death of actor Natasha Richardson, a 60% increase in emergency room visits at the Montreals Children's Hospital was found in a study by Keays and Pless. 7 These authors concluded that the media coverage of this celebrity death may have generated anxiety among parents, prompting those who might not otherwise have sought medical care to bring their children to the emergency room. 7 The increase in helmet use in people older than 15 years by 12% and by 18% in provinces with and without helmet mandatory, respectively, might partly be due to the fact that parents using ski helmets are role models for their children.…”
Section: Discussionmentioning
confidence: 98%
“…7 These authors concluded that the media coverage of this celebrity death may have generated anxiety among parents, prompting those who might not otherwise have sought medical care to bring their children to the emergency room. 7 The increase in helmet use in people older than 15 years by 12% and by 18% in provinces with and without helmet mandatory, respectively, might partly be due to the fact that parents using ski helmets are role models for their children. Jung et al 6 reported that children whose parents used ski helmets themselves wore significantly more frequently ski helmets than children whose parents did not wear a helmet.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We are unable to measure what effect this might have had on the responses of the parents in our sample, but it conceivably may have influenced some parents to prefer immediate CT scanning who might not have otherwise. 22 Perhaps the fact that nearly half of parents who stated a preference for immediate CT scanning selected ''I know someone who had bleeding in their brain after a head injury'' as their third most important reason for their preference reflects, in part, this phenomenon.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, media plays a role in affecting the longer-term inflow. Previous studies have found that media coverage of adverse events influences healthcare related behavior, leading to more people seeking care when the media coverage is intense [9, 10]. However, there is little research investigating how ED inflow is affected in the following weeks after a terrorist attack.…”
Section: Introductionmentioning
confidence: 99%